Izdaja Bosne / Betrayal of Bosnia - Trbić, Jusuf (Pregled: časopis za društvena pitanja / Periodical for social issues, 2023)
This text is a review of a book by Dr. Muhamed Borogovac The War in Bosnia and Herzegovina: How Genocide Was Rewarded and Republika Srpska Established, Bloomington: Xlibris, 2019 (printed in USA).